2016
DOI: 10.1111/jsr.12429
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of obstructive sleep apnea–hypopnea syndrome (OSA) population by means of cluster analysis

Abstract: Obstructive sleep apnea-hypopnea syndrome (OSA) is being identified increasingly as an important health issue. It is typified by repeated episodes of upper airway collapse during sleep leading to occasional hypoxaemia, sleep fragmentation and poor sleep quality. OSA is also being considered as an independent risk factor for hypertension, diabetes and cardiovascular diseases, leading to increased multi-morbidity and mortality. Cluster analysis, a powerful statistical set of techniques, may help in investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 18 publications
3
58
0
1
Order By: Relevance
“…Some studies stated that there may not be a causal relationship between OSA and hypertension (Cano-Pumarega et al, 2011), while other studies found no influence of the BMI on these associations (Carlson, Hedner, Ejnell, & Peterson, 1994). Recent studies introduced the cluster analysis approach, forming subtypes based on clinical symptoms to account for OSA heterogeneity (Lacedonia et al, 2016;Ye et al, 2014). They found that the association to CVDs depended on clusters (Ye et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies stated that there may not be a causal relationship between OSA and hypertension (Cano-Pumarega et al, 2011), while other studies found no influence of the BMI on these associations (Carlson, Hedner, Ejnell, & Peterson, 1994). Recent studies introduced the cluster analysis approach, forming subtypes based on clinical symptoms to account for OSA heterogeneity (Lacedonia et al, 2016;Ye et al, 2014). They found that the association to CVDs depended on clusters (Ye et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a small single-centre study, LACEDONIA et al [91] stratified the patients with moderate-severe OSA according to the level of nocturnal hypoxaemia and identified three clusters. Severe nocturnal hypoxaemia was found in relatively young, severely obese patients who accounted for about half of the total sample, whereas elderly patients with mild nocturnal hypoxaemia and few symptoms accounted for ∼8% of the total sample.…”
Section: Clinical Phenotypes Of Osamentioning
confidence: 99%
“…Obesity has been reported to pose a substantial risk for the development of OSAS. Adipose tissues interact with the respiratory system physiologically and pathologically by producing adipocytokines and regulating metabolic and in ammatory processes [34,35]. IL-6 seems to contribute to weight gain in patients with OSAS and can modify the risk of obesity-related metabolic disorders [36].…”
Section: Discussionmentioning
confidence: 99%